Theoretical perspectives and clinical applications of non-coding RNA in lung cancer metastasis: a systematic review - Jie Yang; Yi Luo; Zuhuan Yao; Zhaokai Wang; Ke Jiang (Discover Oncology)
Abstract Lung cancer is one of the deadliest malignancies worldwide, with distant metastasis being a major cause of death. However, the specific mechanisms of lung cancer metastasis remain unclear. NcRNAs, a widely present type of non-coding RNAs in the body, constitute about 98% of the human genome, lacking protein-coding capacity but involved in various cellular processes such as proliferation, apoptosis, invasion, and migration. Studies have shown that ncRNAs play a crucial role in the metastasis of lung cancer, although research in this area is limited. This review summarizes the biological origins and functions of ncRNAs, their specific roles and mechanisms in lung cancer metastasis, and discusses their potential for early screening and therapeutic applications in lung cancer. Furthermore, it outlines the challenges in translating basic advancements of ncRNAs in lung cancer metastasis into clinical practice.